The role of FOXP3+ regulatory T cells in human autoimmune and inflammatory diseases. (24th March 2019) - Mohr, A; Atif, M; Balderas, R; Gorochov, G; Miyara, M
Summary: CD4 + regulatory T cells (Treg ) expressing the forkhead box protein 3 (FOXP3) transcription factor (Tregs ) are instrumental for the prevention of autoimmune diseases. There is increasing evidence that the human T regulatory population is highly heterogeneous in phenotype and function. Numerous studies conducted in human autoimmune diseases have shown that Treg cells are impaired either in their suppressive function, in number, or both. However, the contribution of the FOXP3 + Treg subpopulations to the development of autoimmunity has not been delineated in detail. Rare genetic disorders that involve deficits in Treg function can be studied to develop a global idea of the impact of partial or complete deficiency in a specific molecular mechanism involved in Treg function. In patients with reduced Treg numbers (but no functional deficiency), the expansion of autologous Treg cells could be a suitable therapeutic approach: either infusion of in-vitro autologous expanded cells, infusion of interleukin (IL)-2/anti-IL-2 complex, or both. Treg biology-based therapies may not be suitable in patients with deficits of Treg function, unless their deficit can be corrected in vivo / in vitro . Finally, it is critical to consider the appropriate stage of autoimmune diseases at which administration of Treg cellular therapy can be most effective. We discuss conflicting data regarding whether Treg cells are more effectual at preventing the initiation of autoimmunity, ameliorating disease progression or curing autoimmunity itself. Graphical Abstract: